Rate and Associated Factors of Post-Traumatic Stress Disorder in Elderly Survivors of Bombardment in Ilam City, Iran - A. Rostamizadeh; Y. Abolfathi Momtaz; M. Foroughan (Afarand Scholarly Publishing Institute, 2020)
Aims: The psychological effects of war, such as post-traumatic stress disorder, may persist for years after the war. The aim of this study was to estimate the rate of post-traumatic stress disorder and its related factors in the elderly survivors of the bombing in Ilam. Instrument & Methods: The present study was performed by retrospective cohort method on 227 elderly survivors of the imposed war living in Ilam City, Iran, in 2019 who were selected by multi-stage proportional random sampling. The NSESSS-PTSD instrument was used to measure post-traumatic stress disorder. Used descriptive and inferential statistics (independent t-test, ANOVA, and Correlation) for data analysis by SPSS 23 software. Findings: The mean age of the elderly participating in the study was 66.67±7.16 years. 54.2% of participants were female. There was a significant relationship between marital status, employment, witnessing injuries and deaths, age at wartime and gender, and post-traumatic stress disorder. There was a significant relationship between current chronic patients and post-traumatic stress disorder. Conclusion: 16.3% of the elderly survivors of the bombing of the Iran-Iraq war in Ilam have post-traumatic stress disorder.